Microscopic and Mesoscopic Dual Postsynthetic Modifications of Metal–Organic Frameworks. (3rd June 2020) - Lee, Byeongchan; Moon, Dohyun; Park, Jinhee
Abstract: We report the dual postsynthetic modification (PSM) of a metal–organic framework (MOF) involving the microscopic conversion of C−H bonds into C−C bonds and the mesoscopic introduction of hierarchical porosity. MOF crystals underwent single‐crystal‐to‐single‐crystal transformations during the electrophilic aromatic substitution of Co2 ( m ‐DOBDC) ( m ‐DOBDC 4− =4, 6‐dioxo‐1, 3‐benzenedicarboxylate) with alkyl halides and formaldehyde. The steric hindrance caused by the proximity of the introduced functional groups to the coordination bonds reduced bond stability and facilitated the transformation into hierarchically porous mesostructures by etching with in situ generated protons (hydroniums) and halides. The numerous defect sites in the mesostructural MOFs are potential water‐sorption sites. However, since the introduced functional groups are close to the main adsorption sites, even methyl groups are able to considerably decrease water adsorption, whereas hydroxy groups increase adsorption at low vapor pressures. Abstract : It takes two : Microscopic and mesoscopic dual postsynthetic modifications of metal–organic frameworks introduced hierarchical porosity while converting C−H bonds into C−C bonds (see picture). Owing to the proximity to the open Co sites, the introduced functional group could effectively prevent or enhance the adsorption of guest molecules.